Seismic Anisotropy Reveals a Dynamic Link Between Adjacent Magmatic Segments Prior to Dyke Intrusion. Issue 11 (8th November 2018) - Illsley‐Kemp, Finnigan; Greenfield, Tim; Keir, Derek
Abstract: Seismic anisotropy has increasingly been proposed as a tool in the monitoring of magmatic systems and potential forecasting of volcanic eruptions. We present a detailed study of how seismic anisotropy evolves in an active magmatic rift segment before, during, and after a dyke intrusion in the Afar depression, Ethiopia. Results show that seismic anisotropy prior to the dyke intrusion is controlled by a complex and deforming magma plumbing system beneath the adjacent Dabbahu and Manda‐Hararo magmatic segments. Approximately eight days prior to the dyke intrusion in the Dabbahu segment, the pattern of anisotropy, coupled with lower crustal seismicity, is best explained by the inflation of a lower crustal magma reservoir in the Manda‐Hararo segment. This is the only clearly observed precursory change in seismic anisotropy. During the dyke intrusion, the magnitude of seismic anisotropy increases twofold, before rapidly returning to predyke values once the intrusion has ended. Combining our observations with models of magmatically induced crustal stress, we propose that when the deep magma reservoir beneath the Dabbahu segment becomes overpressured, inflation is triggered in the magma reservoir of the neighboring Manda‐Hararo segment. This provides strong evidence for a hydraulic link between the deep magma systems of the neighboring rift segments and that magma reservoirs beneath the Dabbahu segment can be fed by the lateral flow of magma from an adjacent segment. Our results demonstrate that seismic anisotropy has the potential to be a powerful tool for monitoring deformation in the magma plumbing systems of active volcanoes. Key Points: We detail time‐varying, crustal seismic anisotropy around a dyke intrusion in the Afar depression The magnitude of seismic anisotropy is shown to increase during the dyke intrusion, suggesting pressurization of the hydrothermal system Change in anisotropy prior to dyke intrusion reveals inflation of magma chamber in adjacent rift segment, suggesting lateral flow of magma